KEEFEKTIFAN MEDIA SCRET OF SCREEN (SOS) MELALUI MODEL STUDENT TEAM ACHIEVEMENT DIVISIONS ( STAD) TERHADAP HASIL BELAJAR BENDA DAN SIFATNYA - Diani Dewi, Tara; ., Suyitno; Prima A, Filia (Universitas Pendidikan Ganesha, 2018)
This study aims to determine the effectiveness of SOS media through the STAD model on learning outcomes of objects and the nature of third grade students of Ringin Kidul Elementary School when learning in learning completeness and student learning outcomes. This research is a quantitative study with a form of design. Pre Experimental Design which is a form of One Group Pretest-Posttest Design. The percentage of classical completeness initially 40% to 85%, the mastery of learning increased by 45%. The results of the analysis using the t test obtained value t = 8,568> t table = 1,725. From the results of the above research it can be concluded that SOS media through the STAD model is effective against the results of learning objects and the nature of third grade students of SDN Ringin Kidul. Key words: Effectiveness, Science, Scret Screen of Screen, STAD Model, Learning Outcome.